ASPECTOS ECOLÓGICOS DOS METAZOÁRIOS ENDOPARASITAS DE Hoplias malabaricus NO PANTANAL SUL-MATOGROSSENSE - MINHOS, Liandra Ferreira; COSTA, Fábio Edir Dos Santos; VIEIRA, Kelly Regina Ibarrola; FERREIRA, Rayane Oliveira; MOTA, Rafael Da Silva (ANAIS DO ENIC, 2017)
-